Ontology-Based Approach for Liver Cancer Diagnosis and Treatment. - Messaoudi, Rim; Mtibaa, Achraf; Gargouri, Faiez; Jaziri, Faouzi; Grand-Brochier, Manuel; Ali, Hawa Mohamed; Chabrot, Pascal; Vacavant, Antoine; Amouri, Ali; Fourati, Hela (Journal of Digital Imaging, 2019)
Liver cancer is the third deadliest cancer in the world. It characterizes a malignant tumor that develops through liver cells. The hepatocellular carcinoma (HCC) is one of these tumors. Hepatic primary cancer is the leading cause of cancer deaths. This article deals with the diagnostic process of liver cancers. In order to analyze a large mass of medical data, ontologies are effective; they are efficient to improve medical image analysis used to detect different tumors and other liver lesions. We are interested in the HCC. Hence, the main purpose of this paper is to offer a new ontology-based approach modeling HCC tumors by focusing on two major aspects: the first focuses on tumor detection in medical imaging, and the second focuses on its staging by applying different classification systems. We implemented our approach in Java using Jena API. Also, we developed a prototype OntHCC by the use of semantic aspects and reasoning rules to validate our work. To show the efficiency of our work, we tested the proposed approach on real datasets. The obtained results have showed a reliable system with high accuracies of recall (76%), precision (85%), and F-measure (80%).